Apremilast in comorbidities associated with psoriasis - Parasramani, Shrichand; Mishra, Pallavi; Dhoot, Dhiraj (International Journal of Research in Dermatology, 2026)
Psoriasis (PsO) is a multifactorial inflammatory disorder frequently associated with comorbidities such as cardiovascular disease (CVD), metabolic syndrome (MetS), and type 2 diabetes mellitus (DMII). Several studies have demonstrated a strong correlation between PsO and MetS, suggesting shared inflammatory mechanisms. Chronic inflammation contributes to both conditions, with cytokines such as tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-17, and IL-10 playing central roles. IL-17, in particular, modulates the interface between inflammation and metabolism by influencing glucose homeostasis and adipocyte function. Elevated TNF-α and IL-6 levels, characteristic of PsO, are implicated in insulin resistance, while IL-6 additionally promotes adipose lipolysis and hepatic gluconeogenesis, exacerbating metabolic dysfunction.